2020
DOI: 10.2174/1874306402014010038
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction Among a Sample of Egyptian Patients with Asthma

Abstract: Background: Despite asthma being a worldwide disease, still little awareness regarding the sexual function of asthmatic patients exists. So this study attempts to assess the Female Sexual Dysfunction (FSD) amongst Egyptian females with asthma and its burden on their quality of life. Materials & Methods: The sample consisted of 180 subjects, comprising 90 asthma patients and 90 healthy controls aged between 20 - 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 24 publications
0
14
1
1
Order By: Relevance
“…In our study, it was determined that the Sexual Quality of Life increased as the education level increased. Some studies have reported sexual dysfunction decreases and the quality of sexual life increases as the level of education increases, hence, education level is an important risk factor for the development of sexual dysfunction [ 11 , 15 ]. In this study, the low quality of sexual life of patients with a low level of education can be explained by their lack of knowledge about sexuality, perceiving sexuality as taboo, accepting the situation with the understanding of weakness, not being comfortable to talk about sexuality and accepting it as learned concepts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, it was determined that the Sexual Quality of Life increased as the education level increased. Some studies have reported sexual dysfunction decreases and the quality of sexual life increases as the level of education increases, hence, education level is an important risk factor for the development of sexual dysfunction [ 11 , 15 ]. In this study, the low quality of sexual life of patients with a low level of education can be explained by their lack of knowledge about sexuality, perceiving sexuality as taboo, accepting the situation with the understanding of weakness, not being comfortable to talk about sexuality and accepting it as learned concepts.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was determined that the quality of sexual life decreased with increasing age. Studies have shown that sexual life and functions are negatively affected by increasing age [ 10 , 11 , 13 , 15 , 24 ]. It is known that as age increases, hormonal changes in individuals, decrease in the capacity of organ functions and physical disability cause an increase in sexual dysfunction [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among females, particularly the asthmatic patients, the most common SD was diminished arousal, followed by loss of desire and orgasm difficulty [25, 27]. The emotional well-being of the patients had a remarkable impact on the overall FSFI score, whereas domains such as intercourse satisfaction, lubrication, and pain were less affected by allergic diseases and showed minimal changes even after the improvement of allergic symptoms [31]. Based on these findings, we assume that psychological stress and depression play a primary role in SD of female allergic patients, which disinterest them to perform sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic comorbid medical conditions may also have effects on sexual function due to symptoms, sequelae, and/or required medications associated with the disease. This can be the case with inflammatory bowel diseases like Crohn's disease ( 10 ), diabetes mellitus ( 11 ), epilepsy ( 12 ), cardiovascular and respiratory conditions ( 13 , 14 ), and hepatic, urinary, and reproductive health conditions ( 15 – 17 ).…”
Section: Introductionmentioning
confidence: 99%